Beyond the Market. Recognizing those who take care of water - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2011)
From the start of the 1990s, the issue of Environmental Services has attracted the attention of conservationists, development organizations and donors, who have been interested in seeking and supporting new strategies for financing conservati on and, additionally, in some cases, for diversifying the income of rural communities.By the logic of the market, the principal proposal is the Payment for Ecosystem Services: “a voluntary transaction for an environmental service, in which at least one buyer and one seller participate; the environmental service is well-defined; and the provider of the service ensures its provision”. Given that water in the Andes is such an important resource, closely related with the management of ecosystems and important for the wellbeing of dozens of millions of people, we can assume that there exists a large market for the Payment of Hydrological Ecosystem Services (PHES).